Validity of regional network systems on reperfusion therapy in diabetes mellitus and non-diabetes mellitus patients with ST-segment elevation myocardial infarction - Li, Xicong; Lu, Lifei; Yuan, Qi; Yang, Lixia; Du, Liping; Guo, Ruiwei (Frontiers in Cardiovascular Medicine, 2022)
Background: Patients with ST-segment elevation myocardial infarction (STEMI) with diabetes mellitus (DM) have higher mortality and poorer prognoses than those without DM. Previous studies have demonstrated the effectiveness of regional network systems (RNS) for reperfusion therapy in patients with STEMI. However, the differences in nursing care with RNS in subgroups of patients with DM with STEMI are unclear. Our study aimed to evaluate the validity of RNS in reperfusion therapy in patients with STEMI with or without DM. Methods: We retrospectively enrolled patients with STEMI who received reperfusion therapy at the chest pain center of the 920th Hospital in Kunming City, Yunnan Province from 2019 to 2021. Personal information and hospitalization information for patients with STEMI were collected through the chest pain center registration system. Univariate and multivariate logistic regression were used to analyze factors for patients with STEMI who received RNS. Wilcoxon rank-sum test and chi-squared test were used to analyze the differences in reperfusion therapy times and clinical outcomes between RNS and non-RNS in patients with STEMI with or without DM. Results: This study enrolled 1,054 patients with STEMI, including 148 patients with DM and 906 patients without DM. Logistic regression analysis showed DM was associated with patients with STEMI who received RNS [OR 1.590 95% CI (1.034 – 2.446), P = 0.035]. RNS may decrease the reperfusion therapy time in patients with STEMI and patients without DM with STEMI, including the first medical contact (FMC) to door, FMC to wire and FMC to catheterization laboratory activity (all P < 0.05). However, we found no significant difference in reperfusion therapy times with and without RNS in patients with DM (all P > 0.05). Conclusion: RNS may decrease the reperfusion therapy time in patients without DM with STEMI, but no decrease was found in patients with DM with STEMI.